Role of dinoprostone gel in induction of labour - Patel, Meet S.; Jani, Shashwat K.; Patel, Babulal S.; Shah, Akshay C. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
Background: Labour induction is one of the most common intervention in obstetric practice. A simple application of PGE2 intracervical gel can ripen the cervix effectively and improve Bishop’s score there by helping in successful vaginal delivery. Considering its good performance, the dinoprostone slow-release vaginal insert is the first choice for elective induction of labour in postdate pregnancy and in patients with term pregnancy of premature rupture of membranes. Methods: This was a single year retrospective study conducted in a tertiary care center of western India from May 2019 to May 2020. Results: In group I women who delivered within 24 hours were included, in group II women who required re-instillation were included. The most common indication for induction in both the groups was past dates (accounting for 36.1% in group I and 47.3% in group II). The success rate in group I was 68.1% while in group II was 36.8%. The rate of cesarean delivery in group I was 25.9%, while in Group II, it was 60.1%. Negligible maternal and neonatal complications were seen in both the groups. Conclusions: The study showed that intracervical application of prostaglandin E2 is an effective, safe and acceptable method for induction of labor in women with unfavorable cervix and indications for induction. All these effects were achieved without increasing maternal and neonatal morbidity